2017
DOI: 10.1182/blood-2016-09-736686
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of acute promyelocytic leukemia treated with all-trans-retinoic acid, arsenic trioxide, and gemtuzumab

Abstract: The combination of all--retinoic acid (ATRA) plus arsenic trioxide (ATO) has been shown to be superior to ATRA plus chemotherapy in the treatment of standard-risk patients with newly diagnosed acute promyelocytic leukemia (APL). A recent study demonstrated the efficacy of this regimen with added gemtuzumab ozogamicin (GO) in high-risk patients. We examined the long-term outcome of patients with newly diagnosed APL treated at our institution on 3 consecutive prospective clinical trials, using the combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
200
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(209 citation statements)
references
References 44 publications
6
200
2
1
Order By: Relevance
“…Consequently, patients with low-or intermediate-risk APL 30,31 and with high-risk APL show higher longterm and leukemia-free survival with ATRA-ATO. 32 In addition, the advantages of ATRA-ATO over ATRA chemotherapy increase over time, showing significantly greater and more sustained antileukemic efficacy. 30,32 It remains unknown whether prognostic markers that were previously related to inferior outcomes in APL will retain their clinical relevance in the ATRA-ATO era or whether they will be needed considering the encouraging results with this regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, patients with low-or intermediate-risk APL 30,31 and with high-risk APL show higher longterm and leukemia-free survival with ATRA-ATO. 32 In addition, the advantages of ATRA-ATO over ATRA chemotherapy increase over time, showing significantly greater and more sustained antileukemic efficacy. 30,32 It remains unknown whether prognostic markers that were previously related to inferior outcomes in APL will retain their clinical relevance in the ATRA-ATO era or whether they will be needed considering the encouraging results with this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, the advantages of ATRA-ATO over ATRA chemotherapy increase over time, showing significantly greater and more sustained antileukemic efficacy. 30,32 It remains unknown whether prognostic markers that were previously related to inferior outcomes in APL will retain their clinical relevance in the ATRA-ATO era or whether they will be needed considering the encouraging results with this regimen. For example, Cicconi et al demonstrated that fms-related tyrosine kinase 3-internal tandem duplication mutations had no impact on either event-free survival or CIR in low-risk and intermediate-risk patients receiving ATRA and ATO regimens as first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The outstanding results reported from several albeit nonrandomized trials with the use of GO in recurrent APL and the combination of GO, all-trans-retinoic acid, and arsenic trioxide in the treatment of patients with newly diagnosed high-risk APL make these attractive treatment approaches as well. 34,42,43 Going forward, the most fruitful studies of GO itself may be those investigating the implications of CD33 splice variation and those that attempt to improve our understanding of the cellular basis for susceptibility to GO, focusing on GO uptake and trafficking, sensitivity to DNA damage, and expression of CD33 by the AML stem cell. The recent approval of midostaurin for FLT3-mutated AML and CPX-351 for therapy-related AML or AML with myelodysplasia-related changes presents the additional challenge of defining the relative benefits of these 3 drugs in specific subsets of AML and whether (and how) they can be effectively and safely combined.…”
Section: Going Forwardmentioning
confidence: 99%
“…Relapse of APL after frontline ATRA 1 arsenic trioxide 1 GO has been exceedingly unusual (4%) with long-term follow-up, including patients with presenting white blood cell count of .10 3 10 9 /L. 67,68 Summarizing all the available phase 3 data from 5 phase 3 trials in adults, a UK National Cancer Research Instiute meta-analysis studied 3325 patients treated in these studies. 69 The metaanalysis showed a statistically significant reduction in relapse rates and improved OS for GO-treated patients across these trials, without appreciable increases in toxicity.…”
Section: Targeted Chemotherapy Deliverymentioning
confidence: 99%